Penatausahaan Aset Tetap pada Pemerintah Daerah dengan Opini BPK Wajar dengan Pengecualian (WDP) - Roni Yanto (Pusat Riset dan Inovasi Nasional, 2022)
Managing and managing assets properly and correctly is a must for agencies or local governments. Because assets are a very important thing in describing the wealth owned by an agency or institution for both operational use and for financial reserves in the future. Managing assets for local governments is an obligation based on Government Regulation Number 38 of 2008 concerning Management of Regional Property. In order to ensure that there is good arrangement and management of regional assets, the law provides space for the Supreme Audit Agency (BPK) to audit financial statements and assets owned by a region so that from the results of the examination, Unqualified Results (WTP) can be obtained. , Fair With Exceptions (WDP), Not Fair (TW) and Not Expressing an Opinion (TMP). It all depends on how the region is able to manage and make reports properly in accordance with the provisions of the legislation.